Training on the Implementation of Simple Financial Report Recording in EduPark Pond Tourism in Cangkring Village, Krembung Sidoarjo - Hanif Dzaky Rahmatullah; Pegy Dwi Yuliani Purwanto; Tri Sukma Yuwana; Slamet Dwi Chandra; M. Handri Ansah; Andini Bina Fauziah; Naswa Faqrizah Al-Widad; Ika Putri Susilowati; Fitriana Dewi; Fikha Nur Anisa; Nasywa Anindya Wiraputri; Achmad Room Fitrianto (Talenta Publisher, 2026)
Good financial management is crucial for the sustainability of community-based tourism ventures, such as Cangkring Edupark in Krembung District, Sidoarjo Regency. However, its management often faces challenges due to the lack of systematic financial recording. This program aimed to provide training for Cangkring Edupark managers in preparing simple financial reports, involving students from the Accounting major at UIN Sunan Ampel Surabaya and local village officials. The training utilized the Asset-Based Community Development (ABCD) approach by leveraging local assets. Activities included observation, socialization, training, monitoring, and evaluation to enhance participants's understanding of cash flow recording, profit/loss calculation, and financial reporting. The empowerment efforts resulted in a significant improvement in the managers ability to independently perform simple bookkeeping. This program is expected to serve as a model for empowerment that can be applied to other local tourism destinations in Cangkring Village.